Property Rights, Protest, and the Siting of Hazardous Waste Facilities - Mitchell, Robert Cameron; Carson, Richard T. (American Economic Review, 2016)
ture. Since that time no major HWF has been sited anywhere in the United States. The EPA had anticipated that local opposition would make finding these sites an exceptionally difficult task. Their pessimism was well founded and, if anything, understated. According to the Hazardous Waste Counsultant's latest state-by-state review, the outlook for siting HWFs in the future is even more bleak than in the past, due in large part to what they term a worsening of the emotional atmosphere surrounding siting efforts. This failure to site any new HWF has come about in spite of assurances by government and company officials that new facilities built according to the present standards would pose negligible risks to the local residents. Attempts have been made to break the deadlock by instituting extensive public participation procedures, establishing state siting boards with the power to overrule local decision makers, and requiring facility owners to compensate local governments for safety services the latter provided. In this paper, we argue that the ambiguous nature of the present property rights governing the siting of HWFs is an important cause of the stalemate. We offer a new approach to siting which recognizes the de facto property rights assumed by local communities. We propose a political market, via a referendum